Review of the subtribe Gyrophaenina Kraatz 1856 (Coleoptera: Staphylinidae: Aleocharinae: Homalotini) of Middle Asia, with emphasis on the fauna of Kazakhstan - Enushchenko, Ilya V. (Zootaxa, 2019)
A taxonomic and biogeographic review of thirteen species of Encephalus Stephens 1832 and Gyrophaena Mannerheim 1830 (Aleocharinae: Gyrophaenina) of Middle Asia, with an emphasis on the fauna of Kazakhstan is provided. Gyrophaena (s.str.) aryanamensis Enushchenko, sp. nov. from Tajikistan and Kyrgyzstan, and G. (s.str.) hochhuthi Bernhauer 1908 are re-(described) and illustrated. Several synonymies are established: Encephalus (s.str.) angusticollis Sahlberg 1880 = E. solskyi Heyden 1880 (replacement name of E. kraatzi Solsky 1875; not synonym of G. nitidula (Gyllenhal 1810)), resyn., = E. torosus Eppelsheim 1893, syn. nov.; G. (s.str.) affinis Mannerheim 1830 = G. glareicola Pace 2010, syn. nov., = G. kangasi Rutanen 1994, syn. nov., = G. ranongensis Pace 2005, syn. nov., = G. rosskotheni Wüsthoff 1937, syn. nov. Illustrations of habitus and sexual characters of E. angusticollis are provided. A key to the species of Gyrophaena of the laetula group of Kazakhstan is given. Several members of Gyrophaenina are recorded for the first time: E. angusticollis, G. (s.str.) bihamata Thomson 1867, G. (s.str.) congrua Erichson 1837, G. (s.str.) joyi Wendeler 1924, G. (s.str.) obsoleta Ganglbauer 1895, G. (Phaenogyra) strictula Erichson 1839 from Kazakhstan and Middle Asia, and G. (s.str.) hochhuthi from Kazakhstan, Kyrgyzstan, and China.